The Expression Pattern and Functional Analysis of Extracellular Vesicle Long Non-Coding RNAs from Uterine Fluid During Implantation in Pig - Yijun Shang; Qiuping Zhang; Yue Ding; Yongzhong Wang; Shengchen Gu; Xupeng Zang; Zheng Xu; Sixiu Huang; Zicong Li; Zhenfang Wu; Ting Gu; Linjun Hong; et al. (Animals)
Long non-coding RNAs (lncRNAs) act as competing endogenous RNAs and play significant roles in porcine embryo development. Extracellular vesicles (EVs) in the uterine fluid (UF) can target and deliver maternal endometrial signalling molecules to embryonic trophoblast cells, exerting crucial regulatory effects during embryo implantation. However, the specific roles of lncRNAs carried by UF-EVs during the embryo implantation period have not been thoroughly reported in the literature. In the present study, high-throughput sequencing and biological tools were applied to analyse lncRNAs in UF-EVs on days 9, 12, and 15 of pregnancy to identify key regulatory lncRNAs in UF-EVs during the porcine embryonic implantation period and to explore their expression patterns and functional roles. A total of 30,203 lncRNAs were identified and 7879 differentially expressed lncRNAs were screened, and qRT-PCR was used to verify the sequencing data. Days 9–12 of pregnancy represent a critical stage of embryo implantation characterised by substantial morphological changes in porcine embryos. During this period, we identified a total of 4348 differentially expressed lncRNAs. Through screening and validation, we discovered that LNC_026212 was highly expressed on day 12 of pregnancy and can promote the proliferation and migration of porcine trophoblast cells (PTr cells). These novel findings contribute to our understanding of the impact of lncRNAs on porcine reproductive processes, offering new research directions to improve the success rate of embryo implantation in pigs.